Differential equations can be used to find the rate of change of a function with respect to another function. In this blog post we will discuss how to find the rate of change from an equation.

Before we dive into the details let’s recall what a differential equation is. A differential equation is an equation which contains derivatives of a function. In other words a differential equation is an equation that relates a function and its derivatives.

Now that we have refreshes our memory on differential equations let’s see how we can use them to find the rate of change of a function. Let’s consider the following equation:

y = x^2

Differentiating both sides of the equation with respect to x we get:

dy/dx = 2x

Thus we can see that the rate of change of the function y with respect to x is 2x. In other words the function y is increasing at a rate of 2x.

Now let’s consider another equation:

y = 3x + 5

Differentiating both sides of the equation with respect to x we get:

dy/dx = 3

Thus we can see that the rate of change of the function y with respect to x is 3. In other words the function y is increasing at a rate of 3.

As we can see finding the rate of change of a function from an equation is quite simple. All we need to do is to differentiate the equation with respect to the variable that we are interested in. In the above examples we were interested in finding the rate of change of the function y with respect to x. However we can easily find the rate of change of the function y with respect to any other variable.

Differential equations can be used to find the rate of change of a function with respect to another function. In this blog post we have discussed how to find the rate of change from an equation. We hope that this blog post has been helpful.

## How do you find the rate of change from an equation?

You can find the rate of change by taking the derivative of the equation.

## What is the rate of change of the equation y=x^2?

The rate of change of the equation y=x^2 is 2x.

## What is the rate of change of the equation y=2x+5?

The rate of change of the equation y=2x+5 is 2.

## What is the rate of change of the equation y=-3x+2?

The rate of change of the equation y=-3x+2 is -3.

## What is the rate of change of the equation y=5x^2-4x+3?

The rate of change of the equation y=5x^2-4x+3 is 10x-4.

## What is the rate of change of the equation y=4x^3+3x^2-2x+1?

The rate of change of the equation y=4x^3+3x^2-2x+1 is 12x^2+6x-2.

## What is the rate of change of the equation y=-5x^4+2x^2+3x-4?

The rate of change of the equation y=-5x^4+2x^2+3x-4 is -20x^3+4x+3.

## What is the rate of change of the equation y=2x^5-3x^4+4x^3-5x^2+6x-7?

The rate of change of the equation y=2x^5-3x^4+4x^3-5x^2+6x-7 is 10x^4-12x^3+12x^2-10x+6.

## What is the rate of change of the equation y=-3x^6+4x^5-5x^4+6x^3-7x^2+8x-9?

The rate of change of the equation y=-3x^6+4x^5-5x^4+6x^3-7x^2+8x-9 is -18x^5+20x^4-20x^3+18x^2-14x+8.

## What is the rate of change of the equation y=x^7-2x^6+3x^5-4x^4+5x^3-6x^2+7x-8?

The rate of change of the equation y=x^7-2x^6+3x^5-4x^4+5x^3-6x^2+7x-8 is 7x^6-12x^5+15x^4-16x^3+15x^2-12x+7.

## What is the rate of change of the equation y=-4x^8+5x^7-6x^6+7x^5-8x^4+9x^3-10x^2+11x-12?

The rate of change of the equation y=-4x^8+5x^7-6x^6+7x^5-8x^4+9x^3-10x^2+11x-12 is -32x^7+35x^6-36x^5+35x^4-32x^3+28x^2-24x+20.

## What is the rate of change of the equation y=x^9-2x^8+3x^7-4x^6+5x^5-6x^4+7x^3-8x^2+9x-10?

The rate of change of the equation y=x^9-2x^8+3x^7-4x^6+5x^5-6x^4+7x^3-8x^2+9x-10 is 9x^8-16x^7+21x^6-24x^5+25x^4-24x^3+21x^2-16x+9.

## What is the rate of change of the equation y=-5x^10+6x^9-7x^8+8x^7-9x^6+10x^5-11x^4+12x^3-13x^2+14x-15?

The rate of change of the equation y=-5x^10+6x^9-7x^8+8x^7-9x^6+10x^5-11x^4+12x^3-13x^2+14x-15 is -50x^9+54x^8-56x^7+56x^6-54x^5+50x^4-45x^3+36x^2-26x+14.

## What is the rate of change of the equation y=x^11-2x^10+3x^9-4x^8+5x^7-6x^6+7x^5-8x^4+9x^3-10x^2+11x-12?

The rate of change of the equation y=x^11-2x^10+3x^9-4x^8+5x^7-6x^6+7x^5-8x^4+9x^3-10x^2+11x-12 is 11x^10-20x^9+27x^8-32x^7+35x^6-36x^5+35x^4-32x^3+27x^2-20x+11.

## What is the rate of change of the equation y=-6x^12+7x^11-8x^10+9x^9-10x^8+11x^7-12x^6+13x^5-14x^4+15x^3-16x^2+17x-18?

The rate of change of the equation y=-6x^12+7x^11-8x^10+9x^9-10x^8+11x^7-12x^6+13x^5-14x^4+15x^3-16x^2+17x-18 is -72x^11+78x^10-80x^9+80x^8-78x^7+72x^6-64x^5+54x^4-42x^3+30x^2-18x+6.